2017
DOI: 10.1158/1541-7786.mcr-16-0376
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis Identifies MEN1 and MAX Mutations and a Neuroendocrine-Like Molecular Heterogeneity in Quadruple WT GIST

Abstract: Quadruple wild-type (WT) gastrointestinal stromal tumor (GIST) is a genomic subgroup lacking KIT/PDGFRA/RAS pathway mutations, with an intact succinate dehydrogenase (SDH) complex. The aim of this work is to perform a wide comprehensive genomic study on quadruple WT GIST to improve the characterization of these patients. We selected 14 clinical cases of quadruple WT GIST, of which nine cases showed sufficient DNA quality for whole exome sequencing (WES). NF1 alterations were identified directly by WES. Gene ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
59
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 44 publications
1
59
0
5
Order By: Relevance
“…Recently, we and others reported a handful of gene fusions in GIST 47 (Table 1). However, here we report a novel, previously unreported PRKAR1B-BRAF gene fusion in a patient with GIST (Figure 2).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, we and others reported a handful of gene fusions in GIST 47 (Table 1). However, here we report a novel, previously unreported PRKAR1B-BRAF gene fusion in a patient with GIST (Figure 2).…”
Section: Discussionmentioning
confidence: 97%
“…3 We and others recently reported that a small subset of GISTs also occur due to kinase fusions (eg, ETV6-NTRK3 , FGFR1-TACC1 , FGFR1-HOOK3 ), a previously unappreciated mechanism for GIST tumorigenesis. 47 …”
mentioning
confidence: 99%
“…Interestingly, MEN1 and MAX mutations, along with NF1 and SDH, further extend the list of genes detected in KIT/PDGFRA WT GIST, genes which are characteristic for neuroendocrine tumors. Moreover, detection of high expression level of genes involved in the neural commitment process, such ASCL1 and EPHA4, further support the hypothesis of a neuroendocrine like signature for some quadruple WT GIST [32].
Fig.
…”
mentioning
confidence: 56%
“…Moreover, two fusion genes involving FGFR1 were reported in three cases of quadruple WT GIST (FGFR1–HOOK3 and FGFR1–TACC1) [30]. Recently, other fusion events (KIT–PDGFRA, MARK2-PPFIA1 and SPRED2-NELFCD) have also been detected [31, 32]. Finally, relevant somatic mutations, including TP53, MEN1, MAX, CHD4, FGFR1, CTDNN2, CBL, ARID1A, BCOR and APC were also identified [3033].…”
mentioning
confidence: 99%
“…Most KIT/PDGFRA mutated GISTs respond to the RTK inhibitor imatinib; however, treatment response is mainly depending on tumor genotype. [10][11][12] In contrast, the SDH-deficient GIST group includes the majority of pediatric GISTs, some sporadic adult/young adult cases, and rare syndromic GISTs developing in association with the Carney-Stratakis-Syndrome and the Carney triad. Over the last years, it became apparent that the so-called "WT-GIST group" is quite heterogeneous with regards to clinical phenotype and molecular characteristics.…”
Section: Introductionmentioning
confidence: 99%